Controlling the time evolution of mAb N‐linked glycosylation, Part I: Microbioreactor experiments. (27th June 2016) - Villiger, Thomas K.; Roulet, Anaïs; Périlleux, Arnaud; Stettler, Matthieu; Broly, Hervé; Morbidelli, Massimo; Soos, Miroslav
Abstract : N‐linked glycosylation is of key importance for the efficacy of many biotherapeutic proteins such as monoclonal antibodies (mAbs). Media components and cell culture conditions have been shown to significantly affect N‐linked glycosylation during the production of glycoproteins using mammalian cell fed‐batch cultures. These parameters inevitably change in modern industrial processes with concentrated feed additions and cell densities beyond 2 × 10 7 cells/mL. In order to control the time‐dependent changes of protein glycosylation, an automated microbioreactor system was used to investigate the effects of culture pH, ammonia, galactose, and manganese chloride supplementation on nucleotide sugars as well as mAb N‐linked glycosylation in a time‐dependent way. Two different strategies comprising of a single shift of culture conditions as well as multiple media supplementations along the culture duration were applied to obtain changing and constant glycosylation profiles. The different feeding approaches enabled constant glycosylation patterns throughout the entire culture duration at different levels. By modulating the time evolution of the mAb glycan pattern, not only the endpoint but also the ratios between different glycosylation structures could be modified. © 2016 American Institute of Chemical Engineers Biotechnol. Prog ., 32:1123–1134, 2016